Necesidad de reformar el artículo 101 del código orgánico monetario y financiero, para garantizar los derechos de los usuarios de los servicios financieros, de valores y seguros en el Ecuador - Mora Ordoñez, Luis Eduardo (2017)
The problem object of study in which livelihood development of my legal research in applied character has strict relation to the field of public finances, from the perspective of the monetary and financial Organic Code, legal body that governs in Ecuador since the 12 September of the year 2014 and that has been the subject of extensive debate within the legal and economic forum, as well as society in general by the implications and economic effects that have been generating from their validity. The object and scope of regulation of the rules in reference is the starting point that allows us to situate ourselves in the space to investigate, for this it is necessary to mark that articles 1 and 2 of the Organic Code refer it aims to regulate the monetary and financial systems, as well as the regimes of securities and insurance of Ecuador; as well as this code sets the framework of policies, regulations, supervision, control and accountability that governs the monetary and financial systems, as well as the regimes of securities and insurance, the exercise of their activities and the relationship with its users. The point of debate that motivates my study focuses on the means of payment in the Ecuador and particularly on the use of electronic money to carry out commercial transactions of use and recurrence common among citizens regardless of economic activity to develop; in that regard the monetary and financial organic code in its article 99 refers that are means of payment currencies other than the dollar of the United States of America, checks, transfers by electronic means or digital, credit and debit cards and others of a similar nature, in the terms that determine and regulate the Board of policy and monetary and financial regulation. It should be noted that the terms of the law, electronic money is a means of payment which is administered by the Central Bank, which is only exchanged by means of electronic devices, mobile, Electromechanical, smart cards, computers and other regulated by the Board of policy and monetary and financial regulation. Then there is the dispute with the recognition of electronic money as a means of payment in Ecuador, by the existing risk of the lack of guarantees and regulations to strengthen and ensure the money and the user who uses this means of payment, first by the monopoly of the Central Bank, which becomes the sole entity that manages and monitors their use and mainly by the economic crisis in the country.